Exploring Deferoxamine-B for resensitization and antimicrobial resistance mitigation in drug resistant Klebsiella pneumoniae and Staphylococcus aureus: an in vitro study - Abhirami; Satheesh, Arundhathi; Joemon, Adheena; Sathar, Sajmi; Narayanan, Silpa Kannanpallil; Sadanandan, Harish Kumar Kaleeckal (International Journal of Research in Medical Sciences, 2025)
Background: The rising incidence of antimicrobial resistance (AMR) in pathogens like Klebsiella pneumoniae and Staphylococcus aureus is a major global concern. Resistance mechanisms such as extended spectrum β-lactamases (ESBLs), metallo β-lactamases (MBLs), and methicillin resistance limit treatment options. Iron-chelating siderophores like DFO-B may disrupt bacterial iron metabolism and potentially resensitize resistant strains to antibiotics. Methods: This in vitro cross-sectional study assessed the adjunctive effect of DFO-B with selected antibiotics against clinical isolates of MDR K. pneumoniae and S. aureus. Isolates were identified, and antibiotic susceptibility was determined using disc diffusion and micro broth dilution. Synergy between DFO-B and antibiotics was evaluated by disc diffusion enhancement and MIC reduction assays. Results: Among 100 K. pneumoniae isolates, 54% were multidrug-resistant and 46% extensively drug-resistant; 83% produced ESBLs and 70% showed MBL activity, with high resistance to third-generation cephalosporins. DFO-B alone showed no antibacterial effect and did not enhance antibiotic activity, displaying indifferent interactions and mild antagonism with imipenem in ESBL producers. Among 128 S. aureus isolates, tigecycline showed 100% susceptibility in both MSSA and MRSA, with no additional effect from DFO-B. Cefdinir and ampicillin showed higher resistance in MRSA, but their activity improved in the presence of DFO-B, with cefdinir showing a marked increase in MRSA susceptibility and ampicillin showing modest improvement. Conclusion: DFO-B did not enhance antibiotic activity against MDR K. pneumoniae, but it showed some potential to increase susceptibility in selected S. aureus strains. These results highlight the complex role of siderophore-mediated iron chelation in AMR and the need for further research to optimize such combination therapies.